Progression of Cerebellar Atrophy in Spinocerebellar Ataxia Type 2 Gene Carriers: A Longitudinal MRI Study in Preclinical and Early Disease Stages - Nigri, Anna; Sarro, Lidia; Mongelli, Alessia; Pinardi, Chiara; Porcu, Luca; Castaldo, Anna; Ferraro, Stefania; Grisoli, Marina; Bruzzone, Maria Grazia; Gellera, Cinzia; Taroni, Franco; Mariotti, Caterina; et al. (Frontiers in Neurology, 2020)
Spinocerebellar ataxias type 2 (SCA2) is an autosomal dominant inherited disease caused by expanded trinucleotide repeats (≥ 32 CAG) within the coding region of ATXN2 gene. Age of disease onset primarily depends on the length of the expanded region. The majority of subjects carrying the mutation remain free of clinical signs for few decades (“presymptomatic” stage), but in proximity of disease onset subtle neurophysiological, cognitive, and structural brain imaging changes may occur. Aims of the present study are to determine the time-window in which early clinical and neurodegenerative MRI changes may be identified, and to evaluate the rate of the disease progression in both preclinical and early disease phases. We performed a 1-year longitudinal study in 42 subjects: 14 SCA2 patients (mean aged 39 years, disease duration 7 years, SARA score 9 points), 13 presymptomatic SCA2 subjects (preSCA2, mean age 39 years, expected time to disease onset 16 years), and 15 gene-negative healthy controls (mean age 33 years). All participants underwent genetic test, neurological examination, cognitive tests, and brain MRI. Evaluations were repeated at 1-year interval. Baselines MRI evaluations in SCA2 patients showed significant atrophy in cerebellum, brainstem, basal ganglia and cortex compared to controls, while preSCA2 subjects had isolated volume loss in the pons, and cortical thinning in specific frontal and parietal areas, namely rostral-middle-frontal and precuneus. One-year longitudinal follow-up demonstrated, in SCA2 patients, volume reduction in cerebellum, pons, superior cerebellar peduncles, and midbrain, and only in the cerebellum in preSCA2 subjects. No progression in clinical or cognitive measures was observed in preSCA2 subjects. The rate of volume loss in the cerebellum and subcortical region greatly differed between patients and preSCA2. In conclusion, our pilot study demonstrated that MRI measures are highly sensitive to identify longitudinal structural changes in SCA2 patients, and in preSCA2 up to a decade before expected disease onset. These findings may contribute in the understanding of early neurodegenerative processes and may be useful in future therapeutic trials.